Vaccine Hesitancy Status of Parents with 0-48 Months Old Children Registered in Educational Family Health Center; Cross-Sectional Analysis - Z. Yelda Özer; Duygu Korkmaz Yalçın; Alp Çalı; Mevlüde Hümeyra Bilgin; Aslı Boz (Journal of Medical Education and Family Medicine)
Objective: In recent years, especially with the increase in vaccine hesitancy due to the coronavirus disease 2019 (COVID-19) pandemic, the aim has been to study this hesitancy and some sociodemographic characteristics that may influence it among parents with children aged 0–48 months registered at the Educational Family Health Center (EFHC).Methods: This cross-sectional study included parents of children aged 0--48 months who applied to the Çukurova University Çarkıpare EFHC between 12.02.2024 and 08.03.2024. The sociodemographic data and the VVS were administered by interns to the parents who agreed to participate in the study.Results: In this study, which analyzed data from parents (n=52), 61.5% (n=32) of the participants were female. The percentage of those who had received all their vaccinations was 90.4% (n=47), whereas the percentage of those who had vaccinated their children was 92.3% (n=48). The mean total score calculated from the scale was 17.52±8.71. While there was no statistically significant difference in the mean vaccine hesitancy scores across the categories of gender, number of children, education level, income level, place of residence, whether they had been vaccinated and whether their children had been vaccinated (P > .05), a statistically significant difference in the mean vaccine hesitancy scores was found across the categories of the age variable (P < .05).Conclusion: The vaccine hesitancy score calculated in this study was not high, and among the sociodemographic characteristics examined, only age had an effect on vaccine hesitancy, with vaccine hesitancy increasing as the average age increased. It is recommended that the study be further explored through focus group discussions by increasing the number of observations.